The association between physical activity and mental health in medical postgraduates in China during COVID-19 pandemic - Yue, Cai-Ling; Ge, Xing; Liu, Man; Zhang, Beibei; Koda, Stephane; Yan, Chao (Frontiers in Psychiatry, 2022)
Background: Chinese medical postgraduates (CMPs) are a special subpopulation that has a great risk of mental health due to high workload, and heavy academic and clinical pressure during the COVID19 pandemic. Physical activity has been demonstrated to be positive for the mental health of the human being. However, little is known about the risks to mental health among CMPs as well as the potential effects of physical activity on mental health in CMPs during the COVID19 pandemic. Aims: In the present study, the aims are to 1) investigate the levels of PA and mental health that CMPs had; 2) to identify the potential factors that contribute to mental health among CMPs; 3) to explore the potential effects of PA on the mental health in CMPs Methods: The survey was conducted online across 26 provinces of mainland China in 28 medical colleges or universities with structured questionnaires. Physical Activity Rating Scale-3 (PARS-3), Depression, Anxiety, Stress Scales (DASS-21), and General Self-Efficacy Scale (GSES) were employed to assess the levels of PA, Negative emotional states, and self-efficacy of the participants, respectively. Resilience was evaluated using Connor–Davidson Resilience Scale (CD-RISC). The chi-square and Wilcoxon rank-sum tests were used to compare inter-group differences in demographic data and mental health conditions. Spearman's rank correlation test and partial correlation analysis were used to assess associations between exercise scores and mental health. Results: We found some socio‑demographic variables such as the location, education levels of parents and the levels of degrees they are training had potential effects on outcomes of mental health among 2217 CMPs (P<0.05); furthermore, we also found that PA was negatively correlated with the negative emotion (r=-0.045, P<0.05) such as depression(r=-0.052, P<0.05), anxiety and stress, (r=-0.051, P<0.05) but positively correlated with the self-efficacy (r=0.143, P<0.001) and resilience (r=0.192, P<0.001) among Chinese postgraduate medical students. Conclusion: we concluded that for Chinese postgraduate medical students, taking part in physical activity would depress negative emotions such as depression, anxiety, and stress, but improve their self-efficacy and resilience, which will benefit them in completing their studies and training.